Comparison of AHP and fuzzy AHP for multi-criteria decision making / Zuhaibudin Sidek - Sidek, Zuhaibudin; Mohd Ramzi, Nur Madihah; Hashim, Hazwani; Mohamad, Siti Nurul Fitriah (Unit Penerbitan UiTM Kelantan, 2019)
Fuzzy Analytical Hierarchy Process (FAHP) is a Multi-Criteria DecisionMaking (MCDM) process that is developed in order to help in making decision based on multi criteriaand objective. This integrated method of Fuzzy Set Theory and classical Analytical Hierarchy Process (AHP) is said can increase the accuracy of selection. The objectives of this paper are to implement FAHP in selecting students for admission to a university and analyze the selection result with the result of classical AHP. The details steps of FUZZY AHP are clearly and numerically stated.